Cognition in virtual reality: assessing user acceptability and feasibility of virtual reality cognitive screening for older adults - Frank Ho-yin Lai; Frank Ho-yin Lai; Benjamin K. Yee; Benjamin K. Yee; Eileen H. J. Wang; Joe Butler; Andrew Graham; Eddie Yip-kuen Hai; Cath Darling; Stephanie Whittington; Julie-anne Lowe (Frontiers in Psychiatry, 2025)
IntroductionThe global demographic shift towards an older population necessitates innovative methods to assess cognitive abilities, particularly spatial working memory, which is crucial for daily living and early detection of neurocognitive conditions like Alzheimer's disease. MethodsThis qualitative study utilised the Virtual Reality Working Memory Task (VRWMT), a semi-immersive VR activity using keyboard navigation, to assess spatial working memory in older adults. Participants were recruited from community centres and categorised by age and technological familiarity. Focus groups evaluated user perceptions based on the Technology Acceptance Model constructs: Perceived Usefulness, Perceived Ease of Use, Attitude Toward Usage, and Behavioural Intention to Use. The study aimed to assess the acceptability and feasibility of VRWMT across diverse populations, examining its navigational simplicity, emotional engagement, and willingness to endorse VRWMT for routine cognitive assessments.ResultsFindings indicated significant variations in perceived usefulness, ease of use, attitude toward using, and behavioural intention to use across different age groups and socio-demographic characteristics. High-technology-familiarity participants found VRWMT easy to use and engaging, while those with low familiarity struggled with navigation and engagement. Socio-demographic factors such as limited digital literacy and lack of standby support impact technology adoption. Higher technological familiarity leads to better acceptance and feasibility of VRWMT.DiscussionVRWMT can enhance cognitive health monitoring and therapeutic interventions. The results highlighted that personalised pathways and user-friendly interfaces can improve accessibility and engagement, making VRWMT a valuable tool for cognitive assessments, as part of Occupational Therapy, in diverse populations.